Course-of-action theory in table tennis: a qualitative analysis of the knowledge used by three elite players during matches - Seve, C.; Saury, J.; Leblanc, S.; Durand, M. (European Review of Applied Psychology, 2005)
The course-of-action theory (J. Theureau, Le Cours d'action: Analyse Sémiologique, 1992) provided the framework for this study, which described how expert table tennis players' mobilized knowledge in relation with their mode of involvement (exploratory and executory). Matches were videotaped during international meets and the verbalizations of the players as they viewed the tapes were collected a posteriori. The data were processed by transcribing the players' actions and verbalizations, decomposing their activity into elementary units of meaning, labeling the constituents of these units, identifying typical exploratory and executory sequences. The results showed that the knowledge mobilized by the players during the matches differed with their mode of involvement. Knowledge was continuously put into relationship with significant elements in the unfolding situation in order to create interpretive chains, and this contributed to building a meaningful world for the players. The players' cognitive activity was thus revealed to be a permanent construction of meaning aimed at reducing uncertainty in situations of competitive interaction.